2001
DOI: 10.1677/joe.0.1690613
|View full text |Cite
|
Sign up to set email alerts
|

Extracts from tumors causing oncogenic osteomalacia inhibit phosphate uptake in opossum kidney cells

Abstract: In oncogenic osteomalacia (OOM), a tumor produces an unknown substance that inhibits phosphate reabsorption in the proximal tubules. This causes urinary phosphate wasting and, as a consequence, hypophosphatemic osteomalacia. To characterize this poorly understood biological tumor activity we generated aqueous extracts from several OOM tumors. Extracts from three of four tumors inhibited, dose-and time-dependently, 32 Porthophosphate uptake by opossum kidney (OK) cells; maximum inhibition was about 45% of untre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…However, these enzymes efficiently abolish the capacity of PTH and parathyroid extracts to inhibit renal phosphate uptake in vitro . Size ultrafiltration experiments also indicate that tumor phosphatonin-minhibin activity is due to small (< 5 kDa) protease-resistant molecules (Miyauchi et al, 1988;Cai et al, 1994;Wilkins et al, 1995;Lajeunesse et al, 1996;Nelson et al, 1996Nelson et al, , 2001Jonsson et al, 2001). These findings are consistent with the notion that the small proteolytically resistant ASARM peptide is a phosphatonin and/or minhibin (Rowe et al, 2004).…”
Section: From Protease Cleavagesupporting
confidence: 76%
“…However, these enzymes efficiently abolish the capacity of PTH and parathyroid extracts to inhibit renal phosphate uptake in vitro . Size ultrafiltration experiments also indicate that tumor phosphatonin-minhibin activity is due to small (< 5 kDa) protease-resistant molecules (Miyauchi et al, 1988;Cai et al, 1994;Wilkins et al, 1995;Lajeunesse et al, 1996;Nelson et al, 1996Nelson et al, , 2001Jonsson et al, 2001). These findings are consistent with the notion that the small proteolytically resistant ASARM peptide is a phosphatonin and/or minhibin (Rowe et al, 2004).…”
Section: From Protease Cleavagesupporting
confidence: 76%
“…3 Fibroblast growth factor-23 inhibits sodium-phosphate co-transporters in the proximal tubular cells of the kidney in vitro (via a decrease in the sodium phosphate transporter-type 2a (NPT2a) transporters). 4 It has also been shown to inhibit 25-hydroxyvitamin D to 1,25-dihydroxyvitamin D. Furthermore, mice injected with fibroblast growth factor-23 showed reduced serum phosphorus levels, increased phosphate excretion and features of osteomalacia. 5 Similarly, most phosphaturic mesenchymal tumours have been found to over-express fibroblast growth factor-23, and thus exhibit clinical features of osteomalacia.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, FGF23 and MEPE expression are closely correlated in Hyp [40]. Moreover, a number of investigators have reported small (<5 kDa), uncharacterized, phosphaturic molecules partially purified from OHO conditioned media [35,52,[54][55][56]100]. Remarkably, the phosphaturic activity of these molecules is resistant to inactivation by a number of proteases.…”
Section: Discussionmentioning
confidence: 99%